2006
DOI: 10.1016/j.molcel.2006.10.009
|View full text |Cite
|
Sign up to set email alerts
|

A Chaperone-Dependent GSK3β Transitional Intermediate Mediates Activation-Loop Autophosphorylation

Abstract: Glycogen synthase kinase 3 (GSK3), a key component of the insulin and wnt signaling pathways, is unusual, as it is constitutively active and is inhibited in response to upstream signals. Kinase activity is thought to be increased by intramolecular phosphorylation of a tyrosine in the activation loop (Y216 in GSK3beta), whose timing and mechanism is undefined. We show that GSK3beta autophosphorylates Y216 as a chaperone-dependent transitional intermediate possessing intramolecular tyrosine kinase activity and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
228
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(245 citation statements)
references
References 35 publications
10
228
0
3
Order By: Relevance
“…3A), which is consistent with a co-translational autophosphorylation mechanism. Very similar kinetics have been reported for HIPK2 [32] and Drosophila dDYRK2 [13], whereas tyrosine autophosphorylation of GSK3b takes place with some delay after translation [14]. Here we show that DYRK1A retains the capacity of autophosphorylating on tyrosine residues after termination of in vitro translation (Fig.…”
Section: Post-translational Tyrosine Kinase Activity Of Dyrk1asupporting
confidence: 88%
“…3A), which is consistent with a co-translational autophosphorylation mechanism. Very similar kinetics have been reported for HIPK2 [32] and Drosophila dDYRK2 [13], whereas tyrosine autophosphorylation of GSK3b takes place with some delay after translation [14]. Here we show that DYRK1A retains the capacity of autophosphorylating on tyrosine residues after termination of in vitro translation (Fig.…”
Section: Post-translational Tyrosine Kinase Activity Of Dyrk1asupporting
confidence: 88%
“…110 An inhibition of the constitutively active kinase GSK-3β is considered to be beneficial, as it is involved in the regulatory inactivation of many anabolic pathways often leading to muscle wasting. [111][112][113][114][115][116] In detail, it has been demonstrated that physical exercise significantly decreases GSK-3β activity in rat skeletal muscle within 10 min of exercise and remained depressed with 30 and 60 min of exercise. 110 In the following part current treatment substances discoveries will be listed (see for detailed therapies 117,118 ).…”
Section: Current News On Biomarker Researchmentioning
confidence: 99%
“…It is indeed not uncommon that (Tyr) autophosphorylation reactions are regulated by binding of cofactors. For example, GSK3β can autophosphorylate on Tyr residues, an activity that is dependent on Hsp90 association 18. Furthermore, p38α autophosphorylation in cells is dependent on association with tumor growth factor‐β‐activated kinase 1/MAP3K7‐binding protein 1 (TAB 1)43.…”
Section: Discussionmentioning
confidence: 99%
“…For some kinases, however, such a distinction cannot be made so clearly. For example, several predominantly Ser/Thr kinases have been shown to also (auto)phosphorylate Tyr residues 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19. The inverse, a Tyr kinase that also (auto)phosphorylates on Ser/Thr residues, is less common, but occurring nonetheless 20, 21.…”
mentioning
confidence: 99%
See 1 more Smart Citation